DILEMA WORK FROM HOME DIMASA PANDEMI STUDI KAWASAN INDUSTRI BEKASI - Dedi Rianto Rahadi; Tuwinanto Nanto (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2021)
The government's policy of implementing the Implementation of Community Activity Restrictions (PPKM) aims to suppress the increasing spread of the Covid-19 virus. Problems arise when the industry is also required to comply with the policy, which in turn has the effect of reducing the activities of employees working in the office. The emergence of clusters in offices and factories is a consideration for companies to implement work from home (WFH) as a solution. Industrial activities continue even though by implementing work from home (WFH) while prioritizing the safety and health of employees and their families. The purpose of the study was to find out the work from home dilemma during the study of the Bekasi industrial area pandemic. Research method with a qualitative approach. The results show that work from home (WFH) is one of the ideal work methods during the COVID-19 pandemic, because it can reduce employees' exposure to viruses at work while maintaining health protocols. Employee productivity can still be maintained by helping the welfare of employees who work at home.